New approaches to Latin American studies - Poblete, Juan, author. Link
1 online resource (262 pages).
Keywords: New Approaches to Latin American Studies: Culture and Power, Vol. 2 provides an examination of the new and defining approaches that have emerged in the field of Latin American Studies in the last decade since 2014.Like its predecessor, this second volume of New Approaches to Latin American Studies is organized using the concept of a turn (as in linguistic or cultural turn) and aims to help both students and faculty, in an eminently interdisciplinary space like Latin American Studies, find new ways of conceptualizing objects and research. Original contributions from experts in their fields provide a discussion that is not meant to be fully comprehensive but concentrates instead on key authors and key texts. In each chapter, the keyword that defines the turn functions as a specific limit that contains the proliferation of references and connections, restricting them to the trajectory of such turn. This second volume includes 11 new chapters covering important transformations during the last decade on the issues, perspectives, and stakes of the field.This book is an expert-produced, reliable, and reader-friendly orientation to the many new areas of research Latin American Studies now encompasses and evidence of the dynamism of this complex field.